Project management : - Heerkens, Gary R. (McGraw-Hill, 2005)
You've been given a project to manage--now what? Project Management provides you with twenty-four lessons detailing the fundamental skills of successful project management. From understanding the project manager's role to working within budgets and leading a team to understanding and becoming comfortable with the basic tools of project analysis, this latest addition to the popular McGraw-Hill Professional Education Series will show you how to: Motivate your team * Develop a configuration plan * Perform financial analyses * Quantify and analyze risks * Manage communication channels * Maximize learning * Document goals and achievements * Perform a successful and seamless hand-off. Effective project management isn't easy. The payoff, however, is huge, both for your organization and your career. Project Management will give you the essential foundation knowledge you need to become a high-performing, well-regarded, and--in all likelihood--well-rewarded project manager.